RNA interference in glial cells for nerve injury treatment. (July 2020) - Lin, Junquan; Jo, Seung Bin; Kim, Tae-Hyun; Kim, Hae-Won; Chew, Sing Yian
Drivers of RNA interference are potent for manipulating gene and protein levels, which enable the restoration of dysregulated mRNA expression that is commonly associated with injuries and diseases. This review summarizes the potential of targeting neuroglial cells, using RNA interference, to treat nerve injuries sustained in the central nervous system. In addition, the various methods of delivering these RNA interference effectors will be discussed.